2010
DOI: 10.3325/cmj.2010.51.406
|View full text |Cite
|
Sign up to set email alerts
|

Multi-type Childhood Abuse, Strategies of Coping, and Psychological Adaptations in Young Adults

Abstract: Aim To retrospectively analyze the rate of multi-type abuse in childhood and the effects of childhood abuse and type of coping strategies on the psychological adaptation of young adults in a sample form the student population of the University of Mostar. MethodsThe study was conducted on a convenience sample of 233 students from the University of Mostar (196 female and 37 male), with a median age of 20 (interquartile range, 2). Exposure to abuse was determined using the Child Maltreatment Scales for Adults, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 63 publications
3
32
0
8
Order By: Relevance
“…The specific associations may be explained by "differential effects model" (Senn and Carey, 2010) where individual maltreatment type leads to specific detrimental developmental outcomes (Lau et al, 2005;Senn and Carey, 2010) including substance use disorders (Arata et al, 2007). According to the "general effects model" (Senn and Carey, 2010), co-occurring (Arata et al, 2007) and multiple episodes of maltreatment, may also predict later psychopathic conditions through poor coping strategies, behavioral maladaptation (Jackson et al, 2014;Sesar et al, 2010), and substance use disorders including cannabis (Arata et al, 2007). Indeed, an earlier study using the same dataset reported that different types of substantiated childhood maltreatment predicted cannabis use disorders overall .…”
Section: Discussionmentioning
confidence: 99%
“…The specific associations may be explained by "differential effects model" (Senn and Carey, 2010) where individual maltreatment type leads to specific detrimental developmental outcomes (Lau et al, 2005;Senn and Carey, 2010) including substance use disorders (Arata et al, 2007). According to the "general effects model" (Senn and Carey, 2010), co-occurring (Arata et al, 2007) and multiple episodes of maltreatment, may also predict later psychopathic conditions through poor coping strategies, behavioral maladaptation (Jackson et al, 2014;Sesar et al, 2010), and substance use disorders including cannabis (Arata et al, 2007). Indeed, an earlier study using the same dataset reported that different types of substantiated childhood maltreatment predicted cannabis use disorders overall .…”
Section: Discussionmentioning
confidence: 99%
“…Daudzos pētījumos izvairīšanās netiek uzskatīta par adaptīvu stresa pārvarēšanas stratēģiju ilgtermiņā (Sesar, Simic, & Barisic, 2010). Turklāt izvairīšanās tiek saistīta ar internalizētām un eksternalizētām grūtībām -depresiju , trauksmi (Blalock & Joiner, 2000), pēctraumatiskā stresa traucējumiem (Street, Gibson, & Holohan, 2005), riskantu uzvedību (Spaccarelli & Fuchs, 1997).…”
Section: Diskusijaunclassified
“…Folkmane un Lazaruss skaidro, ka indivīda pašizjūtu uzlabo tas, ja viņš var atrisināt stresu izraisošas problēmas, turklāt, plānojot problēmas risināšanu, tas var uzlabot savstarpējās attiecības, pozitīvi mainīt kogitīvo novērtējumu un veicināt pozitīvas sekas emocionālajā sfērā (Folkman & Lazarus, 1990; kā minēts Sesar et al, 2010).…”
Section: Diskusijaunclassified
“…Mixed models have proven to be useful when dealing with nested and clustered data (Searle et al, 1992). In our analysis, level 1 refers to the repeated measurements of individuals' depressive symptom scores, level 2 refers to the individual respondent, and level 3 refers to the family cluster to which the respondent belongs.…”
Section: Analytic Modelsmentioning
confidence: 99%